Laboratory investigation results influence Physician's Global Assessment (PGA) of disease activity in SLE. Issue 6 (2nd April 2020) - Aranow, Cynthia; Askanase, Anca; Oon, Shereen; Huq, Molla; Calderone, Alicia; Morand, Eric F; Nikpour, Mandana
Abstract : Objective: To evaluate the impact of laboratory results on scoring of the Physician Global Assessment (PGA) of disease activity in systemic lupus erythematosus. Methods: Fifty clinical vignettes were presented via an online survey to a group of international lupus experts. For each case, respondents scored the PGA pre and post knowledge of laboratory test results (pre-lab and post-lab PGAs). Agreement between individual assessors and relationships between pre-lab and post-lab PGAs, and PGAs and Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) were determined. Respondents were also asked about factors they incorporate into their PGA determinations. Results: Sixty surveys were completed. The inter-rater PGA reliability was excellent (pre-lab intraclass correlation coefficient (ICC) 0.98; post-lab ICC 0.99). Post-lab PGAs were higher than pre-lab PGAs: median (IQR) pre-lab PGA 0.5 (1.05), post-lab PGA 1 (1.3) (p<0.001), with a median (IQR) difference of 0.2 (0.45). In general, all abnormal labs including elevated anti-double stranded DNA antibody level (dsDNA) and low complement impacted PGA assessment. Cases with weakest correlations between pre-lab and post-lab PGA were characterised by laboratory results revealing nephritis and/or haematological manifestations. Both pre-lab and post-lab PGAs correlated with SLEDAI-2K. However, a significantly stronger correlation was observed between post-lab PGA and SLEDAI-2K. Multiple factors influenced PGA determinations. Some factors were considered by an overwhelming majority of lupus experts, with less agreement on others. Conclusions: We found excellent inter-rater reliability for PGAs in a group of international lupus experts. Post-lab PGA scores were higher than pre-lab PGA scores, with a significantly stronger correlation with the SLEDAI-2K. Our findings indicate that PGA scoring should be performed with knowledge of pertinent laboratory results.